Investigating new SNPs of CAST, CAPN and SCD genes in 5’UTR of Bali cattle - Jakaria Jakaria Jakaria; MOKHAMAD FAKHRUL ULUM; DEWI LESTARI; SAMUEL AKWILA; DIAN ERMA WARU TIDOLF SIHITE; RUDY PRIYANTO; MULADNO; CECE SUMANTRI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Jakaria, Ulum MF, Lestari D, Akwila S, Sihite DEWT, Priyanto R, Muladno, Sumantri C. 2020. Investigating new SNPs of CAST, CAPN and SCD genes in 5’UTR of Bali cattle. Biodiversitas 21: 2971-2976. The present investigation aims to explore specific SNPs of Bali cattle, focusing mainly on CAST, CAPN, and SCD genes in 5'UTR. DNA of Bali cattle (25 individuals) from Breeding Centre of Bali cattle in Bali Province, Indonesia, were extracted according to the protocol of GenAID. Amplification of the CAST, CAPN, and SCD genes were designed using the Primer3 program based on reference sequences (access numbers AH014526.2, AH009246.3, and AY241932). Furthermore, the PCR product was sequenced through forward primer sequencing. The data sequence results were analyzed using the Bioedit, MEGA7, Popgen 3.2, and DnaSP6 V6 programs. The results showed that SNPs were detected at g.921C>T and g.922T>G in 5'UTR for the CAST gene between the reference of GenBank AH014526.2 and Bali cattle, but it was monomorphic within the population. The high polymorphism of SNPs was found in g.232G>T for the CAPN gene and g.134A>del for the SCD gene. However, the SNP g.246C>del SCD gene was detected as monomorphic in this region. Moreover, this result shows that low nucleotide diversities (Pi) for CAST, CAPN, and SCD genes in 5'UTR of Bali cattle were 0.00422, 0.00632, and 0.00449, respectively. This finding was important for developing marker-assisted selection (MAS) to improve the meat quality of Bali cattle.